Soap Stock Separation Process - Fazli, Yousef; Tajdari, Majid; Kermani, Parisa (Asian Journal of Chemistry, 2012)
Soap stock is recovered from alkaline neutralization of the crude soybean oil. Soap stock consists of water, soap, neutral oil, phosphatides and unsaponificable matter. Its composition depends on seed quality, oil extraction and refining conditions. Soap stock is the least valuable byproduct from oil processing. This experiment is based on the recovery of phosphatides, neutral oil, fatty acid, colour pigment from soap stock through solvent extraction, precipitation and distillation.